Validation and psychometric properties of the Consumer Financial Protection Bureau Financial Well-Being Scale (CFPB-FWBS) for Polish family caregivers of individuals with rare diseases - Walkowiak, Dariusz; Jabkowski, Piotr; Domaradzki, Jan (Journal of Medical Science, 2025)
Introduction. Caregivers of individuals with rare diseases (RDs) face numerous challenges related to healthcare access, physical and emotional strain, social isolation, and psychological distress; however, financial burden often has the most significant impact on family well-being and the ability to provide adequate care. This study aimed to validate the Consumer Financial Protection Bureau Financial Well-Being Scale (CFPB-FWBS) among caregivers of individuals with RD in Poland.Material and methods. Based on a sample of 942 family caregivers of individuals diagnosed with one of 159 RDs, the validation procedure involved exploratory and confirmatory factor analyses, along with evaluation of internal consistency and interpretability.Results. Analyses supported the unidimensional structure of the Polish CFPB-FWBS. Inter-item correlations were moderate to strong (r = .48–.68), except for Q9, which showed a weaker correlation. PCA confirmed a dominant first component (eigenvalue ≈ 5.7, explaining ~57% of variance), with all items loading adequately. Cronbach’s alpha was high (α = 0.92), and no item removal improved reliability. CFA indicated good model fit (χ²/df = 5.67, CFI = 0.968, TLI = 0.959, SRMR = 0.03, RMSEA = 0.07). Latent scores (0–100 scale) approximated a normal distribution (M = 50.5, SD = 12.1, range = 14–86).Conclusions. The Polish version of the CFPB-FWBS demonstrates strong reliability, structural validity, and meaningful score distributions among caregivers of individuals with rare diseases. These findings support its use as a standardised measure of financial well-being in Poland, enabling research, policy development, and international comparisons.
Keywords: CFPB-FWBS; family caregivers; financial burden; financial well-being; rare diseases